Foxj1 regulates floor plate cilia architecture and modifies the response of cells to sonic hedgehog signalling - Cruz, Catarina (Company of Biologists, 2010)
Sonic hedgehog signalling is essential for the embryonic development of many tissues including the central nervous system, where it controls the pattern of cellular differentiation. A genome-wide screen of neural progenitor cells to evaluate the Shh signalling-regulated transcriptome identified the forkhead transcription factor Foxj1. In both chick and mouse Foxj1 is expressed in the ventral midline of the neural tube in cells that make up the floor plate. Consistent with the role of Foxj1 in the formation of long motile cilia, floor plate cells produce cilia that are longer than the primary cilia found elsewhere in the neural tube, and forced expression of Foxj1 in neuroepithelial cells is sufficient to increase cilia length. In addition, the expression of Foxj1 in the neural tube and in an Shh-responsive cell line attenuates intracellular signalling by decreasing the activity of Gli proteins, the transcriptional mediators of Shh signalling. We show that this function of Foxj1 depends on cilia. Nevertheless, floor plate identity and ciliogenesis are unaffected in mouse embryos lacking Foxj1 and we provide evidence that additional transcription factors expressed in the floor plate share overlapping functions with Foxj1. Together, these findings identify a novel mechanism that modifies the cellular response to Shh signalling and reveal morphological and functional features of the amniote floor plate that distinguish these cells from the rest of the neuroepithelium.